Application of epistemic logic to the analysis of problems of philosophy (Actual Problems of Mind, 2017)
The paper discusses possible applications of the apparatus of epistemic logic to analysis of some philosophical problems.
Keywords: Epistemic logic; doxastic commitments; criteria of rationality